Generalized Poisson distributions for systems with two-particle interactions. (22nd March 2021) - Hameeda, M; Plastino, Angelo; Rocca, M C
Abstract: In a cosmological context, observational best fits for galaxies' distributions in the Universe have been tackled by recourse to different distribution functions. We provide here arguments favoring the formulation of a rather general distribution function (DF), of Poisson origin, describing galaxy clustering. The DF should be useful irrespective of distances or temperatures. We will be discussing distribution function for gravitational interactions.